The next story : life and faith after the digital explosion - Challies, Tim, 1976- (Grand Rapids, Mich. : Zondervan, 2011)
Acknowledging that technology is everywhere, an inescapable aspect of our lives, author and blogger Tim Challies provides guidance and direction for readers who struggle with the changes brought about by the digital revolution. He helps readers understand why digital technology exists and how a Christian can use new technologies with biblical discernment. Even the least technical among us are being pressed from all sides by advances in digital technology. We rely upon computers, cell phones, and the Internet for communication, commerce, and entertainment. Yet even though we live in this "instant message" culture, many of us feel disconnected, and we question if all this technology is really good for our souls. In a manner that's accessible, thoughtful, and biblical, author Tim Challies addresses questions such as: How has life and faith changed now that everyone is available all the time through mobile phones? How does our constant connection to these digital devices affect our families and our church communities? What does it mean that almost two billion humans are connected by the Internet, with hundreds of millions more coming online each year? Providing readers with a framework they can apply to any technology, Tim Challies explains how and why our society has become reliant on digital technology, what it means for our lives, and how it impacts the Christian faith. - Publisher.
Discerning technology -- Understanding technology -- A digital history -- Speaking, truthing, loving, living (communication) -- Life in the real world (mediation/identity) -- Turn off and tune in (distraction) -- More is better (information) -- Here comes everybody (truth/authority) -- Seeing and being seen (visibility and privacy) -- The next story and the story after that.
Includes bibliographical references (p. 199-204).
Keywords: Technology -- Religious aspects -- Christianity; Christianity -- 21st century; Christian life